Imaging Polarized Secretory Traffic at the Immune Synapse in Living T Lymphocytes - Calvo, Víctor; Izquierdo, Manuel (Frontiers in Immunology, 2018)
Immune synapse (IS) formation by T lymphocytes constitutes a crucial event involved in antigen-specific, cellular and humoral immune responses. After IS formation by T lymphocytes and antigen-presenting cells (APC) the convergence of secretory vesicles towards the microtubule organization center (MTOC), and MTOC polarization to the IS, are involved in polarized secretion at the synaptic cleft. This specialized mechanism appears to specifically provide the immune system with a finely-tuned strategy to increase the efficiency of crucial secretory effector functions of T lymphocytes, while minimizing nonspecific, cytokine-mediated stimulation of bystander cells, target cell killing and activation induced cell death (AICD). The molecular bases involved in the polarized secretory traffic towards the IS in T lymphocytes have been the focus of interest, thus different models and several imaging strategies have been developed in order to gain insights into the mechanisms governing directional secretory traffic. In this review we deal with the most widely used, state-of-the-art approaches to address the molecular mechanisms underlying this crucial, immune secretory response.